Comparative study of standard laparoscopic cholecystectomy and single incision laparoscopic cholecystectomy: outcome and complications - Goyal, Kirti Savyasacchi; Utaal, Maneshwar Singh; Bhatia, Pramod Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Laparoscopic cholecystectomy (LC) has evolved to be as gold standard treatment for gall bladder disease and is the most common laparoscopic procedure performed worldwide. In recent times, the innovative techniques of Natural orifice Transluminal Endoscopic Surgery (NOTES) and Single Incision Laparoscopic Surgery (SILS) have been applied as a step forward towards scar less surgery with added benefits of less pain and less analgesic requirement, shorter hospital stay, quick return to work. Methods: A retrospective study of 50 patients admitted with gall bladder disease through outdoor for laparoscopic cholecystectomy from November 2018 to January 2019 in Maharishi Markandeshwar Institute of Medical Sciences and Research Mullana (AMBALA) were randomized into two groups of 25 each for Single Incision Laparoscopic Cholecystectomy (SILC) and standard laparoscopic cholecystectomy (LC) comparing the operative time, outcome and complications. Results: 50 patients admitted to MMIMSR Mullana from November 2018 to January 2019 with gall bladder disease were divided into two groups of 25 each who underwent three port SILC and four port laparoscopic cholecystectomy (4PLC). The average intra-operative time in SILC (80.56 mins) was significantly more than standard laparoscopic cholecystectomy. The average length of stay in the hospital for SILC was 1.8 days (1-3 days), was significantly less than in standard four port laparoscopic cholecystectomy. Incidence of Intraoperative complications were more in SILC than standard LC. Conclusions: SILC as the newer novel technique had better outcomes in terms of cosmesis, early discharge, shorter stay at hospital.